Analysis of the Factors Affecting Bad Credit at PT. Regional Development Bank Bawean Branch - Bela Rozalia; Anita Handayani (Indonesian Vocational Research Journal, 2022)
Background - credit is an activity carried out by banks and other financial institutions with the aim of providing assistance to small and medium-sized communities. in the Bawean area itself, considering that the majority of the community still manages it poorly, the business capital owned is very weak so this is very inherent in rural areas such as in Bawean. With a lack of capital for small entrepreneurs, the business they run cannot run according to what is expected and the business owner limits the space for movement or activity. With this, the bank provides assistance in the form of capital to the community with the aim of opening a business to support business continuity. In addition, in the credit world, it does not always run smoothly as expected, because there are many risks that are experienced in the event of bad credit caused by business owners experiencing a decline in sales caused by the number of existing business competitors, so that it has an impact on people's income. Objectives – The aims of this study were to determine the factors that influence the causes of bad loans at PT. Bank Pembangunan Daerah or Bank Jatim, Bawean Branch. Design/ Methodology/ Approach – This research is a qualitative research with techniques data collection using interviews Findings - The results of this study indicate that the use of credit is business continuity that occurs due to capital assistance from banks to customers who are in need of capital with the aim of opening the customer's business, and the factor causing bad credit is caused by the risks experienced by customers, namely businesses that pioneered by customers experiencing a decline in sales due to competitors, because with competitors it will have an impact on operating income. Research Implications – This research can be used as a reference for companies in particular Credit section to find out what are the factors that influence the occurrence of bad loans. Research Limitations - Research conducted by researchers has limitations, namely: Focusing on customers who have bad credit caused by declining sales and competition, the researcher does not look for other causes.